Angiogenic factors in the pathogenesis and pathophysiology of preeclampsia: A Mini review - Yelumalai, S.; Subramanian, K.; Omar, S.Z.; Qvist, R.; Muniandy, S. (Scientific Publishers India, 2010)
Preeclampsia (PE) the de novo occurrence of hypertension and proteinuria after the 20(th) week of gestation is a major cause of maternal and fetal morbidity worldwide. While the etiology of PE is still unclear, clinical phenotypes have been associated with high circulating levels of anti-angiogenic proteins such as soluble Fms-like tyrosine kinase 1 (sFlt1) and soluble endoglin (sEng). Furthermore PE is associated with low serum free placental growth factor (PIGF) and free vascular endothelial growth factor (VEGF). Since alterations in levels of these factors precede the onset of clinical disease, have these factors may be useful to screen or identify patients at risk for PE. Women with a history of PE have an increased risk of hypertension, and cardiovascular and renal disease Therefore, this raises the possibility of measuring circulating angiogenic proteins in the blood and the urine as a diagnostic and screening tool for PE. The availability of a test to predict PE would be a powerful tool in preventing PE-induced mortality, especially in developing nations, where high-risk specialists are limited. This review will summarize our current understanding of the role of circulating angiogenic proteins in the pathogenesis and clinical diagnosis/prediction of PE.